INTENTION TO USE FINTECH SHARIAH COMPLIANT CROWDFUNDING: A PROPOSAL FOR RESEARCH - Engku Huda Mursyidah Engku Hassan Ashari,; Sakinah Mat Zin, (Journal of Islamic, Social, Economics and Development, 2023)
Financial technology (FinTech) refers to technology-based products and services that aim to improve existing financial services standards and offer new financial solutions that are faster, cheaper, more convenient, and widely available. One example of a rapidly growing FinTech is crowdfunding platforms based on financing, providing small and medium enterprises (SMEs) with easy access to funding. Many countries have issued regulations and licenses for FinTech activities, including Shariah compliant crowdfunding platforms. These platforms provide Islamic financing solutions to SMEs as an alternative to Islamic bank financing. Therefore, for future research, this study develops a strategic framework for FinTech that provides crowdfunding platforms based on Shariah compliant financing, ensuring the acceptance of SMEs in using them. The proposed conceptual framework and measurement items are built from existent various academic literature based on two grounded theories: the Unified Theory of Acceptance and Use of Technology (UTAUT) and Social Presence Theory (SPT). This study contributes to the literature by identifying FinTech as the driver of the Shariah compliant crowdfunding phenomenon and highlighting fruitful avenues for future studies